Kesiapsiagaan dan Mitigasi Bencana Longsor melalui Program Sekolah Siaga Bencana (SSB) - Mohammad Amin Lasaiba (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
Disasters can greatly impact society, especially vulnerable groups such as older people, children, women, and people with disabilities due to their physical, mental, and social limitations. Disaster preparedness programs such as School Disaster Preparedness (SDP) can be a solution to reduce the impact of disasters on vulnerable groups, especially children in schools. Through SDP, students are trained to have appropriate skills, knowledge, and behaviour to deal with disaster situations. The training aims to increase people's understanding of landslides and readiness to face disasters through the SDP program. The training methods include lectures and simulation practices for evacuation. The participants are elementary school students and local communities. The selection of vulnerable groups is based on the social and economic characteristics of the local community. The training results showed that people's understanding of landslides and readiness to face disasters increased after the training. In addition, the training also improved the ability of students and vulnerable groups to evacuate safely and effectively. The SDP program needs to be continuously socialized and supported by relevant parties to ensure optimal landslide disaster preparedness and mitigation in Ambon City.